2021
DOI: 10.2174/1573399817666210101104326
|View full text |Cite
|
Sign up to set email alerts
|

Methylation Profile of miR-9-1 and miR-9-1/-9-3 as Potential Biomarkers of Diabetic Retinopathy

Abstract: Aims: Analysis of the relationship between the methylation profile of miR-9-1 or miRs -9-1 / -9-3 and Diabetic Retinopathy. Background: Diabetic Retinopathy (DR) is a frequent complication of Diabetes mellitus and it has a decisive impact on quality of life, as it is one of the biggest causes of blindness adult population. Levels of microRNA-9 have been shown to be related to diabetes but little is known about its involvement with DR in humans. Objective: To analyze the relationship between the methylatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…One study showed that miR-9 inhibits high glucose-induced proliferation, differentiation and collagen accumulation of cardiac fibroblasts by down-regulation of TGFBR2 [14]. Previous studies suggest that methylation of miR-9-1 and miR-9-3 favors diabetic retinopathy (DR) in patients with diabetes [15]. However, role of miR-9 in DCM has not reported.…”
Section: Introductionmentioning
confidence: 99%
“…One study showed that miR-9 inhibits high glucose-induced proliferation, differentiation and collagen accumulation of cardiac fibroblasts by down-regulation of TGFBR2 [14]. Previous studies suggest that methylation of miR-9-1 and miR-9-3 favors diabetic retinopathy (DR) in patients with diabetes [15]. However, role of miR-9 in DCM has not reported.…”
Section: Introductionmentioning
confidence: 99%
“…The methylation of mi-RNA-9-1 was found to increase the chance of contracting diabetic retinopathy disease by five-fold, and both methylations of mi-RNA-9-1 and mi-RNA-9-3 increased this chance by eight-fold [139]. Additionally, downregulation of mi-RNA-29b is promoted via Dnmt3b, and its overexpression is found to prevent osteoarthritis through the Dnmt3b/mi-RNA-29b/PTHLH/CDK4/RUNX2 axis, thus suppressing chondrocyte apoptosis and extracellular matrix degradation [140].…”
Section: Epigenetic Impactmentioning
confidence: 96%